Effect of Xylanase and Pentosanase Enzymes on Dough Rheological Properties and Quality of Baguette Bread - Mehrdad Mohammadi; Alaleh Zoghi; Mohammad Hossein Azizi (Journal of Food Quality)
The wheat flour baguette bread is one of the most important foods throughout the world. Therefore, improving the quality of this type of white bread has always been of interest. In this study, the effect of xylanase and pentosanase enzymes on the rheological properties of dough and baguette bread characteristics was investigated. Adding xylanase and/or pentosanase had led to improve rheological properties of the dough. Using 0.2 gr pentosanase in 100 g flour significantly strengthened the gluten network of the dough. Also, this treatment had the lowest extensibility and the highest resistance ratio number. The treatment containing 0.6 g xylanase and 0.1 g pentosanase in 100 g flour had a higher moisture content on the first, third, and fifth days of storage time. Regarding the color of the crust of the produced bread, it was found that the addition of both enzymes at higher levels, especially in enzyme mixtures, decreased the brightness of the bread crust. Due to the organoleptic features of breads, adding xylanase and pentosanase enzymes could improve the volume and crumb texture of the bread, but no significant difference was observed in baking uniformity, physical shape, taste, and odor of bread crumbs. In conclusion, the findings in this study indicated that the type of enzymes added and enzyme levels affected dough rheology, bread properties, and quality of the baguette bread significantly.